Exergy analysis of waste heat recovery cogenerative organic rankine cycle - Ustaoğlu, Abid; Ergün, Alper; Erdoğmuş, Ertuğrul; Torlaklı, Hande; Erdoğmuş, Ertuğrul; Ustaoğlu, Abid (My University, 2019)
Conventional technologies used to generate electricity from heat require high temperature and pressure values. This leads to some technical and economic difficulties. With the effect of industrialization, improvements have been achieved in the world's heat utilization technologies. One of the preferred methods for generating electricity from heat sources at low temperatures, such as waste heat, is Organic Rankine Cycle (ORC). In ORC systems, fluids with a high molecular weight and boiling point lower than water are used as working fluids. Electricity is produced by transferring energy in the waste heat to the organic fluid used in ORC system. In ORC systems, where only electricity is produced, significant losses occur which result in reduced efficiency during the conversion of waste heat. Unlike conventional power generation facilities, cogeneration systems, where simultaneous generation of heat and electricity can be realized, enable the utilization of produced heat energy and make the most efficient use of fuel energy. In this study, exergy analysis of cogenerative ORC system was performed in the Engineering Equation Solver (EES) program. Effect of using different input parameters and working fluids on the irreversibility values ??of cogenerative ORC system components was determined.
Keywords: Waste heat; Cogeneration; Organic rankine cycle; Working fluids; Exergy; Atık ısı; Kojenerasyon; Organik rankine döngüsü; Çalışma sıvıları; Ekserji